Effects of Ultramarathon Running on Mitochondrial Function of Platelets and Oxidative Stress Parameters: A Pilot Study - Hoppel, Florian; Calabria, Elisa; Pesta, Dominik H.; Kantner-Rumplmair, Wilhelm; Gnaiger, Erich; Burtscher, Martin (Frontiers in Physiology, 2021)
Only a few studies have evaluated changes in mitochondrial function and oxidative stress associated with ultramarathon running. Invasive biopsies are needed to assess mitochondrial function of skeletal muscle, which may not be well tolerated by some individuals. Platelets (PLTs) as a metabolically highly active and homogenous cell population were suggested as a potentially valuable surrogate to investigate mitochondrial function. Thus, this study was aimed to evaluate mitochondrial function of PLTs and its association with individual race performance and markers of oxidative stress, muscle damage and renal dysfunction. Race performance and mitochondrial function (high-resolution respirometry, HRR) of PLTs using different substrates inducing ROUTINE , LEAK , N-pathway control state (Complex I linked oxidative phosphorylation; CI, OXPHOS), NS-pathway control state (CI+II linked OXPHOS and electron transfer pathway; ET), S-pathway control state (CII linked ET) as well as parameters of oxidative stress and antioxidant capacity, and markers of muscle and renal injury were assessed in eight male ultramarathon runners (26 – 45 years) before, immediately after and 24 hours after an ultramarathon race (PRE, POST and REC). Ultramarathon running induced an increase in LEAK O2 flux of PLT mitochondria and slight, largely non-significant changes in the oxidant/antioxidant balance. Levels of creatine kinase (CK), lactate dehydrogenase (LDH), blood urea nitrogen, and creatinine were all significantly elevated POST and remained high in REC. There were inverse correlations between race time and N-linked substrate state PRE-POST, and changes in CK and LDH levels were significantly related to PLT mitochondrial LEAK and N-linked respiration PRE. Although race-related changes in respirometry parameters of PLT mitochondria were rather small, a somewhat more pronounced increase in the relative N-linked respiration in faster runners might suggest PLT CI as indicator of physical fitness. The higher PLT LEAK PRE and diminished increase of CK during the race may represent a prophylactic preconditioning and the slight but non-significant elevation of the antioxidant potential post-race as a protective consequence of the race-related oxidative stress and potential threat to the kidney. Our findings point towards an interrelationship between mitochondrial function of PLTs, individual fitness levels and extreme physical and metal stresses, which stimulates further research.